Women's Higher Education in the United States New Historical Perspectives (Historical Studies in Education, 2018)
This volume presents new perspectives on the history of higher education for women in the United States. By introducing new voices and viewpoints into the literature on the history of higher education from the early nineteenth century through the 1970s, these essays address the meaning diverse groups of women have made of their education or their exclusion from education, and delve deeply into how those experiences were shaped by concepts of race, ethnicity, religion, national origin. Nash demonstrates how an examination of the history of women's education can transform our understanding of educational institutions and processes more generally.